Removal of endocrine disrupting chemicals (EDCs) using low pressure reverse osmosis membrane (LPROM) - Razak, A. R. A.; Ujang, Zaini; Ozaki, Hiroaki (IWA Publishing, 2007)
Endocrine disrupting chemicals (EDCs) are the focus of current environmental issues, as they can cause adverse health effects to animals and human, subsequent to endocrine function. The objective of this study was to remove a specific compound of EDCs (i.e. pentachlorophenol, C6OCL5Na, molecular weight of 288 g/mol) using low pressure reverse osmosis membrane (LPROM). A cross flow module of LPROM was used to observe the effects of operating parameters, i.e. pH, operating pressure and temperature. The design of the experiment was based on MINITABâ„¢ software, and the analysis of results was conducted by factorial analysis. It was found that the rejection of pentachlorophenol was higher than 80% at a recovery rate of 60 to 70%. The rejection was subjected to increase with the increase of pH. The flux was observed to be increased with the increase of operating pressure and temperature. This study also investigated the interaction effects between operating parameters involved.